Fosfito de potássio na proteção do feijoeiro contra Colletotrichum lindemuthianum e Rhizoctonia solani e nas respostas bioquímicas de defesa - Costa, Bruno Henrique Garcia (2016)
The use of phosphites for disease management in different crops has increased in recent years. However, studies regarding the use of these products in controlling diseases of common bean are scarce. The objective of this work was to verify the potential of potassium phosphite (PP), applied to the aerial part of bean common plants and on seeds, for the control of Colletotrichum lindemuthianum and Rhizoctonia solani, and elucidate the mode of action of these products. The first study was conducted to evaluate the foliar application of potassium phosphites for the control of anthracnose under greenhouse conditions and the biochemical defense responses induced in common bean plants. We also evaluated the detection of phosphite in the plant tissue and the direct toxicity of this product against mycelial growth of C. lindemuthianum. The potassium phosphites reduced the severity of anthracnose and promoted the increase in the activity of enzymes superoxide dismutase, peroxidase, chitinase and β-1,3-glucanase, in addition to increasing lignification and the content of phenolic compounds. Phosphite was detected in the foliar tissues seven days after application, in concentration that promoted the reduction of C. lindemuthianum mycelial growth. The second study was conducted to evaluate the effect of the treatment of bean seeds with PP for controlling R. solani and C. lindemuthianum, in the induction of biochemical defense responses of the plant and compatibility with Rhizobium tropici, nitrogen fixing bacterium. PP promoted greater emergence speed index and increase of 40.1% of plant stand in relation to control, inoculated with R. solani. PP provided the reduction of 56.9% of the area under the anthracnose progress curve, being significantly similar to the treatment with the fungicide. PP increased the activity of enzymes catalase, superoxide dismutase, phenylalanine ammonia-liase and lignification of the leaves. The application of PP to the seeds resulted in higher nodule mass. The number of nodules formed, the content and the accumulation of nitrogen was similar to the control inoculated with R. tropici. PP increased the defense compounds and pathogen control, and is compatible with the inoculation of R. tropici. Thus, spraying of phosphite is a promising technique for integrating disease management methods for common bean crop.